The Role of public procurement in the development of supply chain and trade of family farming (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
Family Farming (FF) is facing a lack of opportunities for the empowerment of small scale producers in rural areas. One of the main problems of FF is its difficulty in entering value chains that make it a profitable activity and encourages its development. In this sense, the inclusion of the FF as a supplier in public procurement is a strategy that has been recently explored in several countries, notably in relation to the School Feeding Programs (SFPs). The objective of this paper is to review the above initiatives. According to this, first a conceptual framework for the definitions of family farming, public procurements and its potential for rural development was presented. Then, in order to conduct an analysis at an applied level, they were selected, studied and compared five international experiences on the inclusion of the FF in public procurement. Finally, reflections and recommendations are suggested.
Keywords: family farming, public procurements; rural development; social feeding programs; agricultural trade